2011
DOI: 10.3109/08039488.2011.560278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high aerobic intensity training in patients with schizophrenia—A controlled trial

Abstract: Background: Patients with schizophrenia have a high risk of cardiovascular disease (CVD). High aerobic intensity training (HIT) improve peak oxygen uptake (VO2peak), net mechanical efficiency of walking and risk factors for CVD but has not been investigated in patients with schizophrenia. Aims: To investigate effects from HIT on VO2peak, net mechanical efficiency of walking and risk factors for CVD in patients with schizophrenia. Methods: 25 inpatients (F20-29, ICD-10) were allocated to either HIT or playing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 31 publications
14
126
2
4
Order By: Relevance
“…No significant changes in CDSS or SF-36 scores were found in a previous study of high-intensity aerobic training administered three times per week for 8 weeks. 9 This study was partially consistent with our results at week 10. In addition, the groups might have had low levels of depression, thereby complicating any improvement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No significant changes in CDSS or SF-36 scores were found in a previous study of high-intensity aerobic training administered three times per week for 8 weeks. 9 This study was partially consistent with our results at week 10. In addition, the groups might have had low levels of depression, thereby complicating any improvement.…”
Section: Discussionsupporting
confidence: 92%
“…2,3 A recent systematic review demonstrated that patients with schizophrenia who participate less in physical activities have experience more negative symptoms, antipsychotic side effects, low selfefficacy, and other unhealthy lifestyle habits. 4 The important mental and physical benefits of exercise in patients with schizophrenia include improvement of symptoms, 5,6 a decreased need for care, 7 improved quality of life, 8 increased cardiorespiratory capacity, 9 increased muscle strength, 10 and increased functional capacity. 5 Studies of physical exercise among patients with schizophrenia have examined aerobic exercise, 6,9,11 which is characterized by repeated rhythmic movements of the large muscle groups of the body, such as those in the arms and legs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in examining the role of vigorous-intensity activity or higherintensity interval training [44]. The safety and efficacy of high-intensity interval training compared to a standard continuous aerobic exercise prescription or comparing different physical activity intensities using a fixed physical activity volume (i.e., time to achieve the same energy expenditure) is to date yet to be reported in schizophrenia.…”
Section: What Is the Optimal Physical Activity Prescription For Peoplmentioning
confidence: 99%
“…Furthermore, it was found that differences in the level of force were significantly different between the experimental group and the control group, which in turn showed no difference in strength. In another study, Jorn Heggelund et al [41] showed that patients with schizophrenia were able to attend to a high intensity training program and consequently improved their VO2 peak. Schizophrenic patients usually have low VO2 peak values, thus increasing mortality rates due to their body composition and other impairments associated with disease.…”
Section: Effects Of Exercise On Physical Health In Schizophreniamentioning
confidence: 98%